Leidenfrost drops: Effect of gravity. (29th April 2015) - Maquet, L.; Brandenbourger, M.; Sobac, B.; Biance, A.-L.; Colinet, P.; Dorbolo, S.
Abstract: A specific experimental set-up has been installed in a large centrifuge facility in order to study different aspects of Leidenfrost drops under high-gravity conditions (5, 10, 15 and 20 times the Earth gravity). In particular, the drop lifetime and more precisely the variations of drop diameter vs. time have shown to be in good agreement with previous experiments and scaling analysis (Biance A.-L. et al., Phys. Fluids, 15 (2003) 1632). Moreover, so-called chimneys are expectedly observed in the large puddles, the distance between two chimneys depending linearly on the capillary length. Finally, the Leidenfrost point, i.e. the temperature above which the Leidenfrost effect takes place, was unexpectedly found to increase slightly with gravity. A qualitative explanation based on a refined model (Sobac B. et al., Phys. Rev. E, 90 (2014) 053011) recognizing the non-trivial shape of the vapor film under the drop is proposed to explain this observation.